Diagnostics of athletes` motor abilities based on magnetic and electrical stimulation of CNS - Shlyakhtov, V. N.; Gorodnichev, R. M. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to identify special aspects of the use of magnetic and electrical stimulation for diagnosing athletes` motor abilities.